SEJARAH PEMERINTAHAN MARGA PEGAGAN ILIR SUKU II DI DESA SUNGAI PINANG - Jane Putri, Devin; Zahrani, Sahrin; Nanda, Shelia; Hudaidah; Yati, Risa Marta (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2024)
Clan rule has existed in South Sumatra since the time of the Palembang Sultanate. Then in the 19th century, the clan developed, marked by the existence of several clans, one of which was the Pegagan Ilir Tribe II clan in Sungai Pinang Village. However, based on the Decree of the Governor of South Sumatra in 1983, the clan system was abolished and then replaced with villages. This research aims to review the history of the Pegagan Ilir Suku II clan which was abolished. The method used is a qualitative method with data collection techniques through interviews and literature. The Tribe II clan was founded when the Dutch came to the Palembang area. This clan was founded in 1860 AD, based in Sungai Pinang Village 1. The leader of the Pegagan Ilir Suku II clan was a Pasirah who was directly elected by the community. The most famous Pasirah was Abdul Cholik, then after his reign it was continued by Haji Malian, namely his son and then continued by his son Haji Muhammad Noer. The development of religion and education in the Pegagan Ilir Tribe II clan is also very good. The conclusion of this research is that the Pegagan Ilir Tribe II clan is a government system led by Pasirah who ruled very well, where during the reign of this Pasirah, Sungai Pinang Village developed both from a religious and educational perspective.